2021
DOI: 10.1101/2021.03.09.434696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contribution of SARS-CoV-2 accessory proteins to viral pathogenicity in K18 hACE2 transgenic mice

Abstract: Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) is the viral pathogen responsible for the current coronavirus disease 2019 (COVID-19) pandemic. To date, it is estimated that over 113 million individuals have been infected with SARS-CoV-2 and over 2.5 million human deaths have been recorded worldwide. Currently, three vaccines have been approved by the Food and Drug Administration for emergency use only. However much of the pathogenesis observed during SARS-CoV-2 infection remains elusive. To gain … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…Importantly, this 2A approach does not remove any viral gene from the viral genome. Although recent data from our laboratory (28) suggest that ORF7a is not essential for SARS-CoV-2 replication in vitro and in vivo (29), it is still largely unknown whether the lack of ORF7a affects some unknown aspects of SARS-CoV-2 pathogenesis. In addition, this also increases the instability concern regarding the reporter gene, as shown in a recent study where a reporter gene fused into the C terminus of ORF7a was not stable (30).…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, this 2A approach does not remove any viral gene from the viral genome. Although recent data from our laboratory (28) suggest that ORF7a is not essential for SARS-CoV-2 replication in vitro and in vivo (29), it is still largely unknown whether the lack of ORF7a affects some unknown aspects of SARS-CoV-2 pathogenesis. In addition, this also increases the instability concern regarding the reporter gene, as shown in a recent study where a reporter gene fused into the C terminus of ORF7a was not stable (30).…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, this new 2A approach does not remove any viral gene from the viral genome. Although recent data from our laboratory (Silvas et al, 2021) suggest that ORF7a is not essential for SARS-CoV-2 replication in vitro and in vivo , it is still largely unknown whether the lack of ORF7a affects some unknown aspects of SARS-CoV-2 infections. In addition, this also increases the instability concern of reporter gene, as shown in a recent study where a reporter gene fused into the C-terminus of ORF7a was not stable (Rihn et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, elucidation of the major FcγR(s) (FcγRI, FcγRIII and/or FcγRIV) engaged by NAbs will help design ultrapotent SARS-CoV-2 Nab therapies (Smith et al, 2012). Here we have taken a step in this direction by introducing GASDALIE mutations to augment FcγR interactions and enhance in vivo potency of CV3-25.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2-nLuc closely mimics the wildtype virus replication kinetics 108 and stably maintains the nLuc reporter over five generations in vitro. Further, ORF7a deletion was 109 recently shown not to affect pathology of the wildtype virus (Silvas et al, 2021). In vivo BLI revealed that the virus spreads from the nasal cavity to lungs to establish infection.…”
Section: Introductionmentioning
confidence: 97%